Prevalence, clinical characteristics and outcomes of high-risk patients treated for severe aortic stenosis prior to and after transcatheter aortic valve implantation availability. (16th February 2015) - Attias, David; Maillet, Jean-Michel; Copie, Xavier; Bonnet, Nicolas; Mesnildrey, Patrick; Benvenuti, Christophe; Benacerraf, Marc; Scheublé, Aliocha; Digne, Franck; Stratiev, Victor; Guyon, Philippe
Abstract: OBJECTIVES: Transcatheter aortic valve implantation (TAVI) has emerged as an effective treatment for high-risk patients with severe aortic stenosis (AS). The aim of our study was to compare the prevalence, characteristics and outcomes of high-risk patients treated prior to and after the availability of TAVI in our high-volume surgical institution. METHODS: Among 879 consecutive patients treated 2 years before ('pre-TAVI era') and after ('modern era') the availability of TAVI in our institution, 83 patients were at high risk [defined by logistic European System for Cardiac Operative Risk Evaluation (EuroSCORE) >20%]. RESULTS: Among all patients treated for severe AS, the prevalence of high-risk patients was higher in the modern era (12.7 vs 4.9%, P < 0.0001). In the modern era, high-risk patients were treated by TAVI in 89% of cases. Despite similar logistic EuroSCORE (34.9 vs 34%, P = 0.96), the clinical characteristics of these patients have evolved: high-risk patients in the modern era were older (85.3 ± 5.9 vs 78.5 ± 6.5 years, P = 0.0005) and presented more frequently with New York Heart Association class III–IV (92.3 vs 61.1%, P = 0.003), while high-risk patients treated by surgical aortic valve replacement in the pre-TAVI era presented more frequently with a critical preoperative status (33.3 vs 7.7%, P = 0.01), lower left ventricular ejection fraction (41 ± 14 vs 49 ± 15%, P = 0.05) and a history of recent myocardial infarction (27.8 vs 6.1%, P = 0.02). The overall 1-year survival was not different for high-risk patients treated in the pre-TAVI era or in the modern era (61 ± 11 vs 68 ± 6%, P = 0.52). CONCLUSIONS: The availability of TAVI has increased the prevalence of high-risk patients treated for severe AS and changed the clinical features of this kind of patients who were rarely surgically treated before. The 1-year survival was similar between pre-TAVI and modern eras.